If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 2(3 + x) = -4(x + 1) -1x + (3 * 2 + x * 2) = -4(x + 1) -1x + (6 + 2x) = -4(x + 1) Reorder the terms: 6 + -1x + 2x = -4(x + 1) Combine like terms: -1x + 2x = 1x 6 + 1x = -4(x + 1) Reorder the terms: 6 + 1x = -4(1 + x) 6 + 1x = (1 * -4 + x * -4) 6 + 1x = (-4 + -4x) Solving 6 + 1x = -4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 1x + 4x = -4 + -4x + 4x Combine like terms: 1x + 4x = 5x 6 + 5x = -4 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 5x = -4 + 0 6 + 5x = -4 Add '-6' to each side of the equation. 6 + -6 + 5x = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = -4 + -6 5x = -4 + -6 Combine like terms: -4 + -6 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| -8(5x+6)=-368 | | 5-2s=1 | | 50x+160=1000 | | (x+6)(x+19)=0 | | 3(-10t-3)+6t=75 | | 5t+s=t-2 | | 4x+3(x-2)=-5(x-4)-6 | | 6u+48=4(u+7) | | 7x=-91 | | 3(5-3p)=87 | | -8-n=-3(2x-4) | | .06x+0.07(18500-x)=1155 | | 4.8+9.2= | | -x-3y=9 | | 9x^2-12x+8=0 | | 5.6p=22.4 | | 63=-3(1-2x) | | x-3-2x=0 | | 3u+7=-5 | | 0.5(-4+6x)=33.3x+66.6(x+9) | | 15x-5=1+12x | | 25x*76= | | 2-3a=7-2(2a+3) | | 7x+6(-x-17)=-109 | | -8(m-8)=120 | | 7x+.43=y | | -9x+4=-6x+17 | | 12x-8=6x+22 | | 7x-6x-102=109 | | 2x+116-116=180-116 | | 7x-(3x+4)=-2(2x-1)+10 | | 2x^4+x^3-9x^2-4x+4=0 |